Socialization of Goat and Sheep Reproduction Management in Bulu Cina Village, Indonesia - Sitepu, Sukma Aditya; Marisa, Julia; Rianto, Aditiya Amanda; Suhut, Anwar (Asian Journal of Community Services, 2023)
The purpose of this community service is to train the local community in Bulu Cina Village, Indonesia, on how to analyze the profits of sheep farming businesses. This will help farmers determine their profits at different levels of ownership. By implementing this community service, the knowledge and abilities of the community can be enhanced. The University of Pembangunan Panca Budi and Gugah Nurani Indonesia use a combination of lectures, discussions, and hands-on training to help farmers improve their sheep farming businesses. The program has been successful in helping farmers understand how to analyze profits and calculate their earnings, leading to more streamlined production and increased revenue for the farmers. As a result, several farmers have reported significant improvements in their income.